Os desafios da educação especial sob a ótica do Plano Nacional de Educação 2014/2024 - BRIGIDA, Sara Soares de Santa (2019)
The main theme of this monograph is Special Education and its challenges, because we understand that the school has the social function of promoting the formal education of students with disabilities, global developmental disorders and high skills / giftedness, and can also be a substitute for regular education . Thus, the overall objective of the study was to analyze the strategies contained in goal 4 of the National Education Plan 2014/2024 under Special Education. For the elaboration of the research, a bibliographical review and a documentary research were used, in order to achieve the general objective of the present study. I have historically characterized the issue of special education in Brazil and the treatment of legislation over time. I also presented the aspects related to the goals and strategies listed in the PNE 2014-2024. The researched literature allowed me to conclude that special education is a paradigm shift that involves political, social and pedagogical actions, valuing diversity, and, fundamentally, bringing structural changes to the school context, both in professionals and in processes. Finally, we understand that this study is only a small contribution to the great challenge of the academic community, education professionals and public policy in bringing tangible solutions to globally implement the schooling of students with special needs, however, we find more important was the fact that we problematize all this discourse that has been advocated in PNE 2014-2024 in the search for recognition and in guaranteeing the historical achievements of social movements and human rights.